The Venezuelan tax manager's trilemma: tax strategy, extreme compliance, or business survival? (Gestión y Gerencia, 2026)
This article examines the complexity of tax management in Venezuela through the "Trilemma Model," which conceptualizes the unavoidable tension between tax strategy, extreme compliance, and business survival. Using a qualitative methodology with a critical-hermeneutic approach and drawing on two decades of the author's experience in tax advisory, it deconstructs the systemic dysfunction that transforms the legal framework into a primary source of uncertainty. The findings reveal decision-making pathologies such as "fiscal cyclothymia" and "organizational schizoid personality," where companies develop parallel structures to navigate the contradiction between formality and survival. It concludes that Venezuelan tax management represents the paradigm of the "postmodern decision-maker in collapse contexts," requiring a new epistemology of tax management based on contextual judgment, ethics of responsibility, and practical wisdom. The study transcends the Venezuelan case, offering an analytical framework applicable to various contexts of high institutional complexity.
Keywords: Critical hermeneutics; institutional complexity; tax management; professional ethics; trilemma